Penggunaan Aq-Wars (Answer Questions Wars) Sebagai Inovasi Media Pembelajaran Ips Di Sekolah Dasar - Andrian Manogu; Dinda Fitri Utami; Melis Khoirotun Nissa (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
The use of learning media is needed in the learning process teaching today. Mainly in combined subjects such as social studies which is a combination of social science material. Many students feel difficulties in understanding social studies learning material so there is a need for media learning that is able to attract the interest and enthusiasm of students to learn. The more often learning media are used in the learning process students will also get bored so that innovation media is needed new learning. The data collection of this research was carried out by observation and interviews to obtain accurate data. The purpose of this research is to find new learning media innovations in social studies learning. Based on the results of research conducted by teachers, they can use innovation AQ-Wars learning media that focuses on students. AQ-Wars is a learner-centered learning media, where participantsstudents can learn while playing with speed in answering problem exactly. With this learning media, students will become more active and can explore their thinking more broadly.